Riflessi d'Oriente Esperienze e memorie di due viaggiatori toscani in Levante (1760-1792) - Pasta, Renato (Biblioteca di storia, 2021)
The book discusses the experience of two Florentine travellers in the Levant from the 1760s to 1792. During their separate stays in Cyprus and in Istanbul they visited the Holy Land, Anatolia and Mesopotamia providing extensive reports on natural history, institutions, local customs and languages as well as data on the economy and the health conditions of the area. Their numerous printed works enjoyed remarkable success and were translated into French and other languages. The inquiry places the authors firmly within the European 'Republic of letters' and testifies to the growing interest for Islam and Ottoman power during the Enlightenment debate on the eve of the French Revolution.